Integrated transcriptome and metabolome analysis reveal the sesquiterpenoid biosynthesis mechanism of Atractylodes chinensis under drought stress - Wu, Ying; Lu, Yao; Ye, Qiuju; Jin, Bingqian; Jiang, Boqian; Wang, Dan; Yin, Haibo (Frontiers in Plant Science, 2026)
IntroductionAs a traditional Chinese medicine abundant in sesquiterpenoids, Atractylodes chinensis has various pharmacological activities. Nevertheless, the synthesis and metabolism mechanisms of its sesquiterpenoids under drought stress are still not fully elucidated.MethodsTherefore, this study investigated changes in sesquiterpenoid component contents, gene expression profiles, and metabolite accumulation of A. chinensis under drought stress.ResultsResults showed that the moderate drought stress (MDS) significantly increased the contents of atractylodin, β-eudesmol, and atractylenolide I. Compared with the control group (CK), 10,528, 9,755, and 10,562 differentially expressed genes (DEGs) were identified in the light drought stress (LDS), MDS, and severe drought stress (SDS) groups, respectively. These DEGs are involved in plant–pathogen interaction, plant hormone signal transduction, plant MAPK signal transduction, and starch and sucrose metabolism. Metabolic analysis detected 2,101, 2,112, and 2,144 differentially accumulated metabolites (DAMs) in the LDS, MDS, and SDS groups, including atractylodin, β-eudesmol, and atractylenolide I. These DAMs are primarily enriched in three pathways: “ABC transporters”, “D-amino acid metabolism”, and “aminoacyl-tRNA biosynthesis”. Furthermore, we screened and characterized the expression patterns of DEGs and accumulation levels of DAMs involved in the sesquiterpenoid biosynthesis pathway. Notably, the genes TRINITY_DN12874_c1_g1, TRINITY_DN114406_c0_g1, TRINITY_DN2331_c0_g2, TRINITY_DN7401_c0_g1, TRINITY_DN11676_c0_g1, along with the compound Germacra-1(10),4,11(13)-trien-12-ol, are speculated to be key genes and critical metabolite responding to drought stress, respectively.DiscussionThese findings enhance our understanding of the mechanisms by which drought stress modulates the sesquiterpenoid biosynthesis pathways in A. chinensis.